DIAGNOSTIC ACCURACY OF ULTRASOUND IN DETERMINING ESOPHAGEAL VARICES IN HEPATIC CIRRHOSIS BASED ON SPLENIC SIZE ASSESSMENT: Esophageal Varices in Hepatic Cirrhosis - Ali, Dr Usman; Ahmed, Saira; Shehzad, Asim; Sajjad, Rabia (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the diagnostic value of spleen size assessment on ultrasound as predictor of esophageal varices in patients of liver cirrhosis, using upper GI endoscopy as the gold standard. Study Design: Cross sectional validation study. Place and Duration of Study: Military Hospital Rawalpindi, from 28 Aug 2012 to 28 Feb 2013. Material and Methods: Biopsy proven cases of liver cirrhosis with no previous history of upper gastrointestinal tract endoscopy (UGIE) were included in the study. The selected 115 patients underwent USG (ultrasonography) of abdomen and splenic size was measured and documented, followed by screening endoscopy for esophageal varices. Findings of the endoscopic examination were recorded. Results: As a predictor of esophageal varices, splenic size was 92.1% sensitive and 57.7% specific, with a positive predictive value of 88.1%, negative predictive value of 68.2% and diagnostic accuracy of 84.3%. Conclusion: The presence of an enlarged spleen is a valid predictor of the presence of oesophageal varices in patients suffering with liver cirrhosis. Therefore, the use of ultrasound abdomen for the assessment of splenic size may help correctly diagnose such patients and help in their timely management.